Nucleotide sequence of reovirus genome segment S3, encoding non-structural protein sigma NS. - Richardson, M A (1983)
This report describes the complete nucleotide sequence of human reovirus (Dearing strain) genome segment S3. Previous studies indicated that this RNA encodes the major non-structural viral polypeptide sigma NS, a protein that binds ssRNAs (Huisman & Joklik, Virology 70, 411-424, 1976) and has a poly(C)-dependent poly(G) polymerase activity (Gomatos et al., J. Virol. 39, 115-124, 1981). The genome segment consists of 1,198 nucleotides and possesses an open reading frame that extends 366 codons from the first AUG triplet (residues 28-30). There is no significant sequence homology between the plus strand of genome segment S3 and that of genome segment S2 determined previously (Cashdollar et al., PNAS 79, 7644-7648, 1982). However, S3 RNA has significant dyad symmetry and regions that can potentially hybridize (delta G = -26 KCal/mole) with S2 RNA. From the predicted amino acid sequence a possible secondary structure for sigma NS protein was determined. Structural features of reovirus RNA and sigma NS are discussed in relation to their role(s) in viral genome assembly.